Antimicrobial activity of extracts and fractions of Euphorbia lateriflora (Schum. and Thonn) on microbial isolates of the urinary tract (2021)
Euphorbia lateriflora is used in ethnomedicine for treating several conditions, including genital and uri nary tract infections (UTI). Although ethnobotanical claims support its use in therapy, there is limited evi dence on its effect on UTI, even though UTI remains a public health problem in Nigeria especially due to increasing antimicrobial resistance. We investigated the activity of E. lateriflora extracts and fractions on bacterial and fungal isolates from symptomatic urinary tract infections and vaginosis respectively. Qualitative phytochemical screening was conducted on dried pulverised leaves. Successive gradient extraction was carried out with the aid of a soxhlet extractor with n-Hexane, ethyl acetate and methanol respectively. Bioactivity guided fractionation was conducted on the ethyl acetate extract using Vacuum Liquid Chromatography. Antimicrobial susceptibility testing by disc diffusion was conducted on test iso lates. Antimicrobial susceptibility of isolates to extracts and fractions was done using the agar well dif fusion technique. Minimum Inhibitory Concentrations (MIC) and Minimum Biocidal Concentrations (MBC) were determined by agar and broth dilutions respectively. Time-kill assay of the ethyl acetate extract was conducted using the viable count technique. Phytochemicals present include saponins, tan nins and flavonoids. The majority of isolates used in this study were multidrug resistant. Extracts and fractions of E. lateriflora produced appreciable zones of inhibition on both antibiotic susceptible and resis tant bacteria with MICs of 6.25 mg/mL and MBC ranging from 6.25–50 mg/mL. Bactericidal activity of the ethyl acetate extract was concentration and time dependent with 100% kill at 25 mg/mL after 6 h for E. coli and 2 h for C. albicans. Euphorbia lateriflora contains phytochemicals which possess antimicrobial activity on antibiotic resistant bacteria and has potential in the development of chemotherapeutics for bacterial and fungal infections.